Growth Attributing Traits of Maize Affected by Different Nutrient Management in Lamjung Nepal - Pal, Manish Kumar; Marasini, Prakash; Ghimire, Salikram (International Journal of Applied Sciences and Biotechnology, 2017)
A field experiment was conducted during the spring season of 2016   at research field of Institute of Agriculture and Animal Science (IAAS), Lamjung, Nepal to evaluate effect of different nutrient management on growth attributing traits of maize. The experiment was laid out in Randomized Complete Block Design (RCBD) having three replications with following treatments; T1( Control), T2 (0.18:0.09:0.06 kg NPK), T3 (3.75 kg vermicompost),  T4 (7.5 kg Poultry manure), T5 (11.25 kg goat manure), T6(15 kg cattle manure) and T7(13 kg Asuro). All these fertilizers were used per plot (15 m2) and the maize variety was Arun-2. The results showed that the application of poultry manure produced the highest plant height, leaf area index and dry matter which was followed by vermicompost.  The application of goat manure gave the highest benefit cost ratio.Int. J. Appl. Sci. Biotechnol. Vol 5(1): 98-101